The Effect of Exclusive Breastfeeding, Nutrition Status, Smoking Habits and Workplace Distance Towards Frequency of Acute Respiratory Tract Infection in Toddlers (Universitas Negeri Semarang, 2019)
Acute Respiratory Tract Infection is one of the causes of children death in developing countries, such as Indonesia. Piyungan Subdistrict, which is one of the sub-districts in Bantul Regency, has many industries and factories which experience an increase of Acute Respiratory Tract Infection cases each year, namely 1004 cases in 2016 and 3124 cases in 2017. The purpose of this study was to analyze the effects of exclusive breastfeeding, nutritional status, smoking habits and the distance of houses from factories to the frequency of Acute Respiratory Tract Infection in toddlers. This research was a correlation analytic with cross-sectional approach. The sampling technique used purposive random sampling of 101 toddlers from a total population of 947. The instruments used were questionnaires and observation sheets. Data analysis used chi-square test and logistic regression. The results showed that exclusive breastfeeding had an effect on the frequency of Acute Respiratory Tract Infection in infants (p-value 0,000; OR 0.081), nutritional status (p-value 0,000; OR 0.017). Smoking habits affect the frequency of Acute Respiratory Tract Infection toddlers and have a risk of 0.17 times to increase the frequency of Acute Respiratory Tract Infection toddlers (p-value 0,000; OR 0.170), while the distance of the house from the factory has an effect on the frequency of Acute Respiratory Tract Infection of children under five and has a risk of 0.212 times greater to increase the frequency of Acute Respiratory Tract Infection in toddlers (p-value 0.001; OR 0.212). Therefore, there is a need for programs that support parents' knowledge and awareness of children nutrition and environmental health to reduce the risk of Acute Respiratory Tract InfectionÂ in toddlers in industrial estates.